Faktor-faktor yang mempengaruhi usaha mikro kecil dan menengah dalam membayar pajak penghasilan - Ali Sandy Mulya (Penerbit Goodwood, 2019)
Purpose: This study aims to provide an overview and empirical evidence about knowledge & understanding of tax regulations, a good perception of the effectiveness of the taxation system, the level of trust in the system of law and government that affects the desire of MSMEs to pay income tax with economic growth as a moderating variable Research methodology: The population in this study was MSME entrepreneurs in South Tangerang City - Indonesia in 2018. The data was processed by using SPSS 22.0 program and WarpPLS 5.0. Results: Knowledge & understanding, good perceptions of the effectiveness of the taxation system and the level of trust in the legal & government system have a significant effect on MSMEs in paying income tax. Economic growth does not moderate the interaction of knowledge, understanding, and the level of trust in the law & government system of MSMEs in paying income tax. Economic growth strengthens the interaction of good perceptions on the effectiveness of the taxation system on MSMEs in paying income tax. Limitations: The samples were only MSMEs in Serpong and Pamulang Subdistrict, South Tanggerang, Indonesia. Contribution: The impact of economic growth encourages MSMEs to pay taxes. This shows that MSMEs can reallocate resources across sectors to the use of the highest-value economy, increase the efficiency, and it can lead to increase the size of the economy. Keywords: Knowledge, Perception, Trust, Growth, Willingness